Perancangan Enterprise Architecture Bimbingan Belajar Menggunakan TOGAF-ADM - Kurniaji, Carlo Rafael; Edyawati, Ellya; Tantono, Rico; Yuardy, Teresa (JATISI, 2025)
The implementation of information technology can be a key factor in improving the quality of tutoring services. However, many institutions do not yet have a structured system architecture framework, which hinders the achievement of business goals. This study aims to design an Enterprise Architecture (EA) in a tutoring institution. Designed using the TOGAF-ADM approach method, to create a structured IT framework that supports improving services and business efficiency by aligning IT strategies with operational needs, identifying gaps, and building an integrated system for data-based decision making. Research methods include analyzing organizational needs, identifying existing conditions, designing business architecture, data architecture, and application architecture in accordance with the ADM stages. The results of the study are in the form of a business process diagram, including system integration, optimization, and development of IT-based services. Using the implementation obtained in the results and discussion, tutoring institutions will increase competitiveness, improve operational efficiency, and optimize resource utilization. In conclusion, the application of TOGAF-ADM as an EA design framework is relevant and contributes to building a more adaptive and oriented information system foundation.